A cohort study on the relationship between education level and high‐risk population of stroke. Issue 3 (28th September 2021) - Yu, Yan‐Yan; Lei, Dan; He, Qiong; Chen, Wei
Abstract : Objective: To explore the relationship between education level and high‐risk population among stroke screening populations in Zunyi City, China. Methods: The cluster sampling method was adopted to collect the medical history, laboratory examinations and physical examinations for the permanent residents of Zunyi City, Guizhou Province. Taking education level as a key socioeconomic status (SES) indicator, multivariate logistic regression analysis was used to evaluate the risk factors of high‐risk groups with different education levels. Results: Among the included 4149 subjects, 494 were in the high‐risk group and 3655 were in the non‐high‐risk group. The proportion of the high‐risk population with education level ≥ high secondary school (8.7%) was significantly higher than that of the low‐risk population. After adjusting for age, gender, and BMI, the OR of those with education leve l ≥ high secondary school was 2.8 (95% CI 1.9‐4.2), which was significantly higher than those with education level of illiterate/primary school. In the model adjusted for all confounding factors, compared with illiterate/primary school, people with education level ≥ high secondary school were more likely to be at high risk of stroke (OR 3.0, 95% CI 1.9‐4.6). Conclusion: Education level ≥ high secondary school is an independent influencing factor for the high‐risk population of stroke in Zunyi, which may be related to smoking and lipid metabolism abnormalities of people with high education level. Key interventions for high‐risk populations with high education levels may have positive significance in reducing the incidence of stroke.